Decoration of Co/Co3O4 nanoparticles with Ru nanoclusters: a new strategy for design of highly active hydrogenation1. Issue 22 (14th June 2015) - Zhu, Lihua; Yang, Zhiqing; Zheng, Jinbao; Hu, Weiwei; Zhang, Nuowei; Li, Yunhua; Zhong, Chuan-Jian; Ye, Hengqiang; Chen, Bing H.
<x xml:space="preserve">Abstract</x> Ru/Co/Co3O4/C (Ru nanoclusters-on-Co/Co3O4 nanoparticles) shows unexpected catalytic activity for benzene hydrogenation via the synergetic effect of Ru, Co and Co3O4 sites.